Coping, meaning in life, and quality of life during ongoing conflict: insights from Israeli populations - Orly Sarid; Liat Hamama; Yaira Hamama-Raz (Israel Journal of Health Policy Research)
Abstract Background Conducted in May 2024, this study examines the well-being of Israeli evacuees and non-evacuees from conflict zones. We assess health-related quality of life (HRQoL), meaning in life (MIL), coping strategies, psychological symptoms, and self-mastery. Aims include exploring effects of trauma and socio-demographics on HRQoL and MIL, analyzing mediating roles of psychological symptoms and coping, and evaluating if evacuation status moderates these relationships during ongoing conflict. Methods In May 2024, seven months post–October 7th attacks, we conducted a cross-sectional study with 366 participants (221 evacuated, 145 non-evacuated) via a survey company. We assessed HRQoL (SF-12), MIL (MLQ), psychological symptoms (PHQ-4), self-related and other-related coping strategies (Brief COPE), and self-mastery (Self-Mastery Scale) through self-reported measures. Path and moderated mediation analyses evaluated relationships among socio-demographics, psychological symptoms, coping variables, HRQoL, and MIL. Results Except for self-mastery, northern and southern evacuees showed no significant differences and were combined into one group. Path analysis revealed significant associations between traumatic life events, HRQoL, and MIL. Traumatic events were negatively associated with the physical component summary (PCS) of HRQoL and positively with anxiety, depression, and coping (self and others- problem-solving). Depression negatively related to PCS, mental component summary (MCS), and MIL, while coping (self and others) was positively associated with MIL. Moderated mediation analysis showed evacuated participants had higher dysfunctional coping, whereas non-evacuated participants demonstrated a stronger positive relationship between anxiety and the search for meaning. Conclusion Despite regional differences, evacuees exhibited similar psychological responses, likely due to the shared experience of displacement. Traumatic events negatively impacted their HRQoL and MIL. Adaptive coping strategies—self-related and problem-focused coping through helping others—played significant roles in mitigating these effects. The theoretical frameworks of Conservation of Resources (COR) theory, Taylor’s “tend and befriend” model, and Frankl’s existential framework provided a basis for explaining these findings.